2010
DOI: 10.5054/tj.2010.227607
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Language Purpose: Vocabulary, Structure, and Function

Abstract: Although learning objectives are a hallmark of lesson planning, it is rare for these to be shared with learners, even though best practices suggest doing so. This article examines the practice of establishing purpose for English language learners as a means for developing conceptual schemas. Participants in this study were 332 southern California K‐12 teachers who submitted 500 examples of the language purposes they used with students. The authors analyzed these surveys and identified the predominant language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…The other targets included verb tenses, wh ‐questions, paragraph writing, one contraction, and one conjunction. These findings are similar to the studies reviewed above (Baecher et al, 2014; Fisher & Frey, 2010; Ranney, 2012) that underscored teachers’ tendency to overemphasize vocabulary over other structures in LOs. For example, one of the objectives that focused on vocabulary for a language target was “Your job today is to match 10 pictures of actions ( cut , pour , add , beat , stand , stir , place , fill , top, and refrigerate ) to their vocabulary word.” This objective for a Level 1 student has the specific vocabulary listed as a language target, a support (pictures), a language function (match), and content connection (recipe reading was a main part of the content objective).…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…The other targets included verb tenses, wh ‐questions, paragraph writing, one contraction, and one conjunction. These findings are similar to the studies reviewed above (Baecher et al, 2014; Fisher & Frey, 2010; Ranney, 2012) that underscored teachers’ tendency to overemphasize vocabulary over other structures in LOs. For example, one of the objectives that focused on vocabulary for a language target was “Your job today is to match 10 pictures of actions ( cut , pour , add , beat , stand , stir , place , fill , top, and refrigerate ) to their vocabulary word.” This objective for a Level 1 student has the specific vocabulary listed as a language target, a support (pictures), a language function (match), and content connection (recipe reading was a main part of the content objective).…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Fisher and Frey (2010) also found that teachers were including activities in their LOs instead of language learning goals. Some of the teachers in their study explained that they would do this because they were trying to go along with the administrative expectation to have a language goal but did not understand how to construct a purpose statement.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These in turn relate to contextual influences, such as whether the instruction takes place in a single period of language instruction or as part of a total immersion program, and if the target language is learned in a highly scripted grammatical model or a content-based environment. Teachers who are focused on the content learning of students may neglect to attend to language form, letting errors go uncorrected and placing their emphasis on meaning rather than accuracy, while teachers who are oriented towards teaching language may provide much in the way of feedback to error and attention to language instruction, but struggle to situate this language in rich content learning (Cammarata, 2009;Fisher & Frey, 2010;Long, 2007). As Lyster (2007) sums up, 'content-based instruction that only alludes to language incidentally falls short of full-fledged integration, and decontextualized grammar instruction, by definition, precludes integration' (p. 26).…”
Section: Planning For Language In Content-based Language Instructionmentioning
confidence: 99%
“…o Conceptualizing Academic Language (Solomon & Rhodes, 1995) o "The Language of Mathematics": Towards a Critical Analysis of Mathematics Texts (Morgan, 1996) o Learning Mathematics Vocabulary: Potential Pitfalls and Instructional Strategies (Thompson & Rubenstein, 2000) o Word, Definitions, and Concepts in Discourses of Mathematics, Teaching, and Learning (Morgan, 2005) o Examining Mathematical Discourse Practices (Moschkovich, 2007) o Let's Talk: Promoting Mathematical Discourse in the Classroom (Stein, 2007) o The Language and Grammar of Mathematics (pp.8-16) in The Princeton Companion to Mathematics (Gowers, Barrow-Green, & Leader, 2008) o Unpacking the Language Purpose: Vocabulary, Structure, and Function (Fisher & Frey, 2010) o Although we are committed to preparing our PSTs to be successful with any performance assessments, it is important to have a balanced perspective and make informed instructional decisions in teacher preparation programs. In particular, we have some concerns regarding the ways edTPA incorporates academic language.…”
Section: What We Did With Our Teacher Candidatesmentioning
confidence: 99%